2021
DOI: 10.1680/jgeen.21.00104
|View full text |Cite
|
Sign up to set email alerts
|

Assessing single-helix screw pile geometry on offshore installation and axial capacity

Abstract: Due to their low-noise installation and relatively large axial capacity, screw piles have been proposed as an alternative foundation solution in dense sand for offshore renewable energy applications in deeper water. For this to occur, a significant upscaling of onshore dimensions is required. Furthermore, the effects of certain geometric features on installation requirements are still not well understood. In this paper, the effects of base geometry, shaft diameter and helix pitch were investigated using the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The prediction of pile axial capacity is depicted in Figure 5 (Cerfontaine et al, 2021b) or loading (Sharif et al, 2021b(Sharif et al, , 2021a of screw piles can be used to enrich experimental findings and develop physically-based prediction methods. Finally, installation in the field will be undertaken at constant vertical force (pile and tool weight), with the AR adapting to maintain the vertical equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…The prediction of pile axial capacity is depicted in Figure 5 (Cerfontaine et al, 2021b) or loading (Sharif et al, 2021b(Sharif et al, , 2021a of screw piles can be used to enrich experimental findings and develop physically-based prediction methods. Finally, installation in the field will be undertaken at constant vertical force (pile and tool weight), with the AR adapting to maintain the vertical equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive experiments [8,13,[21][22][23][24][25][26][27][28][29][30], numerical analyses [12,[31][32][33][34][35][36][37], and theoretical analyses [38][39][40] have been conducted on the load-bearing performance of helix anchors. Tsuha et al [28] performed centrifuge uplift loading tests on 12 different types of piles installed in two sands with different densities to examine the effect of the number of helices on the performance of helical anchors in sand.…”
Section: Introductionmentioning
confidence: 99%
“…Cerfontine et al [41] used the finite element method to predict the full tensile load-displacement response of shallow helix anchors installed in sand for practical use, incorporating the effects of a pitch-matched installation, and found the compression (crowd) load applied during the anchor installation phase modified the stress field around the anchor, which in turn affected the anchor uplift stiffness. The DEM has also been used to investigate the installation effects of helical anchors [31][32][33]. Cerfontine et al [31] found that when a single-helix pile is installed at AR < 1, the soil particles below the helical plate show an upward movement trend.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations